Sea ice primary productivity in the northern Barents Sea, spring 2004 - Andrew McMinn; Hegseth, EN (2007)
The biomass and productivity of sea ice algae was assessed in the northwestern Barents Sea in May 2004. Sea ice algal pigment content was patchy with a mean of 18.5 Â± 8.9 mg Chla m-2. The algal community was dominated by the diatom Nitzschia frigida. Primary production measured by 14C incubations was between 0.37 and 2.8 mg C m-2 h -1, which compared well with oxygen-based methods using the diffusive boundary layer approach (0.071-1.1 mg C m-2 h-1). Given the differences in the irradiances under which these two sets of measurements were made, there was a strong level of consistency between the two sets of results. Measurements of primary production were consistent with previous Arctic measurements but high spatial heterogeneity made a regional estimate of production inappropriate. Â© 2006 Springer-Verlag.